Developing Health Information Systems in Developing Countries: The Flexible Standards Strategy1 - Braa, Jørn; Hanseth, Ole; Heywood, Arthur; Mohammed, Woinshet; Shaw, Vincent (MIS Quarterly, 2007)
The development of appropriate integrated and scalable information systems in the health sector in developing countries has been difficult to achieve, and is likely to remain elusive in the face of continued fragmented funding of health programs, particularly related to the HIV/AIDS epidemic. In this article, we propose a strategy for developing information infrastructures in general and in particular for the health care sector in developing countries. We use complexity science to explain the challenges that need to be addressed, in particular the need for standards that can adapt to a changing health care environment, and propose the concept of flexible standards as a key element in a sustainable infrastructure development strategy. Drawing on case material from a number of developing countries, a case is built around the use of flexible standards as attractors, arguing that if they are well defined and simple, they will be able to adapt to the frequent changes that are experienced in the complex health environment. A number of paradoxes are highlighted as useful strategies, integrated independence being one that encourages experimentation and heterogeneity to develop and share innovative solutions while still conforming to simple standards. The article provides theoretical concepts to support standardization processes in complex systems, and to suggest an approach to implement health standards in developing country settings that is sensitive to the local context, allows change to occur through small steps, and provides a mechanism for scaling information systems.